Survivability in optical networks. - Dongyun Zhou
Survivability, the ability of a network to withstand and recover from failures, is one of the most important requirements of networks. Its importance is magnified in fiber optic networks with throughputs on the order of gigabits and terabits per second. This article takes a look at the techniques used to achieve survivability in traditional optical networks, and how those techniques are evolving to make next-generation WDM networks survivable.
Keywords: WDM networks; Failure recovery; Fiber optic networks; Optical networks survivability; Throughput; Wavelength-division multiplexing